FITOGEOGRAFI PASAK BUMI (Eurycoma longifolia, Jack) PADA KAWASAN HUTAN LINDUNG GUNUNG AMBAWANG BUKIT BENDERA KABUPATEN KUBU RAYA KALIMANTAN BARAT - Le, Mardon Van; Kartikawati, Siti Masitoh; Manurung, Togar Fernando (Universitas Tanjungpura, 2019)
Pasak Bumi (Eurycoma longifolia, Jack.) It is a rare medicinal plant commonly found in Indonesian forests. The purpose of the study was to determine the phytogeography of pasak Bumi in Mount Ambawang Bukit Bendera, Kubu Raya Regency. The study was conducted by survey method with data collection techniques using the census method. The conditions observed included conditions, slope, altitude, and wind direction aspects (North, South, West, East). Then map the census results by measuring stem diameter (cm), tree height (m), slope (%), altitude (m asl), wind direction aspects, and coordinate points. Then true value, with the literature on habitat and phytogeography of pasak Bumi. Based on the results of the study found a total of 91 individuals scattered starting from an altitude of 98-200 m above sea level, the southernmost most found amounted to 45 individuals, the eastern part numbered 17 individuals, the western part amounted to 18 individuals while in the north with the number 11 individuals. This is because growth is covered by a canopy of dense trees that cover the pasak Bumi plant.Keywords: Eurycoma longifolia, Gunung Ambawang, Kubu Ray, pasak Bumi, phytogeography.